A homozygous ABHD16A variant causes a complex hereditary spastic paraplegia with developmental delay, absent speech, and characteristic face. Issue 3 (13th December 2021) - Miyake, Noriko; Silva, Sebastián; Troncoso, Mónica; Okamoto, Nobuhiko; Andachi, Yoshiki; Kato, Mitsuhiro; Iwabuchi, Chisato; Hirose, Mio; Fujita, Atsushi; Uchiyama, Yuri; Matsumoto, Naomichi
Abstract: Hereditary spastic paraplegia (HSP) is a genetically and clinically heterogeneous genetic disease characterized by progressive weakness and spasticity predominantly affecting the lower limbs. Complex HSP is a subset of HSP presenting with additional neuronal and/or non‐neuronal phenotypes. Here, we identify a homozygous ABHD16A nonsense variant in two affected children in a Chilean family. Very recently, two groups reported patients with biallelic ABHD16A whose clinical presentation was similar to that of our patients. By reviewing the clinical features of these reports and our patients, ABHD16A ‐related HSP can be characterized by early childhood onset, developmental delay, intellectual disability, speech disturbance, extrapyramidal signs, psychiatric features, no sphincter control, skeletal involvement, thin corpus callosum, and high‐intensity signals in white matter on T2‐weighted brain MRI. In addition, our affected siblings showed a characteristic face, sleep disturbance, and nodular and hyperpigmented skin lesions, which have not previously been reported in this condition. Abstract : We reported a family with complex hereditary complex paraplegia (HSP) arising from a biallelic ABHD16A pathogenic variant. ABHD16A ‐related HSP is characterized by early childhood onset, developmental delay, intellectual disability, speech disturbance, extrapyramidal signs, psychiatric features, no sphincter control, skeletal involvement, thin corpus callosum, and high‐intensity signals in white matter on T2‐weighted brain MRI. Our affected siblings showed a characteristic face, sleep disturbance, and nodular and hyperpigmented skin lesions, which have not previously been reported.